Barbie girls on blades - Miller, Mona (london egment book ltd, 2004)
Diane and Amy belong to an afterschool in-line blading club. When a competition for prized new skates threatens to destroy a friendship, Barbie helps the girls learn about sportsmanship
3
Keywords: Dolls -- Juvenile fiction; Sportsmanship -- Juvenile fiction